(untitled) (Research, Society and Development, 2022)
This research aims to examine the issue of chemical dependence and the occurrences of epigenetic changes, highlighting its relevance in the clinical care of illegal drug users. For that, a systematic literature review was carried out, according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) model. An electronic search for articles was performed in the databases: Cumulative Index to Nursing and Allied Health Literature (CINAHL); EBSCOhost, EMBASE; Latindex; Literatura Latino-Americana e do Caribe em Ciências da Saúde (LILACS); Medical Literature Analysis and Retrieval System Online/PubMed (MEDLINE); Science Direct, Scientific Electronic Library Online (SciELO), SCOPUS, ISI Web of Science, with the descriptors "epigenetics AND illicit drugs AND addiction OR dependence AND mental disorders AND genetic predisposition OR genetic susceptibility”, chosen in consultation with DeCS and Medical Subject Heading (MeSH). A search strategy resulted in 532 studies. Following the inclusion and exclusion criteria, 22 articles published from 2008 to 2021 in national and international literature were analyzed. This review contributes to direct future research. A greater understanding of the complexities of the epigenome and the unravelling of the effects and contributions of disease states versus drugs of abuse is crucial to the development of new clinical therapies. Epigenetic therapy holds great promise for treating complex diseases and personalized interventions, including psychiatric illnesses.